PENGUATAN KOMPETENSI GURU DALAM PENILAIAN AUTENTIK BERBASIS HOTS (HIGHER ORDER THINKING SKILLS) - Lala Jelita Ananda; Fahrurrozi Fahrurrozi; Didi Febrian (Universitas Negeri Medan, 2019)
Through HOTS (Higher Order Thinking Skills) based authentic learning and assessment assistance conducted at SDN 101766 Bandar Setia for class teachers, the results were obtained that the teachers could carry out HOTS-based authentic learning and assessment in Elementary Schools after obtaining material, training and mentoring from the service team. This mentoring activity was based on the results of preliminary observations at SDN 101766 Bandar Setia, that the teachers did not really understand the authentic HOTS-based learning and assessment and also still had difficulty in applying HOTS to learning. Furthermore, assistance was provided to SDN 101766 Bandar Setia teachers through workshops, training and mentoring activities. Activities carried out in three stages, namely: 1) Preparation; 2) Implementation; 3) Evaluation, and 4) Follow Up. The products produced through this activity are a Book Collection of RPP and HOTS-based Authentic Assessment, HOTS-based Authentic Assessment Handbook, Activity Videos, and Learning Videos.Keywords: authentic assessment, HOTS, competence.